The dual role of vitamin C in cancer: from antioxidant prevention to prooxidant therapeutic applications - Cao, Xiongfeng; Yi, Yide; Ji, Minjun; Liu, Yanfang; Wang, Dongqing; Zhu, Haitao (Frontiers in Medicine, 2025)
Vitamin C (VC), a pleiotropic molecule with context-dependent redox properties, exhibits dual roles in cancer biology through dose-dependent mechanisms. While nutritional VC intake demonstrates chemopreventive effects by scavenging carcinogen-induced reactive oxygen species (ROS) and maintaining genomic stability, high-dose intravenous VC acts as a prooxidant to selectively kill tumor cells via ROS-mediated deoxyribonucleic acid (DNA) damage, adenosine triphosphate (ATP) depletion, and HIF-1α degradation. Preclinical studies reveal VC’s ability to reprogram the tumor microenvironment (TME) through collagen hydroxylation-mediated extracellular matrix remodeling, Treg suppression, and enhancement of CD8+ T cell infiltration. Importantly, VC synergizes with conventional therapies by radio-sensitizing hypoxic tumors through oxygen-sparing effects and reversing platinum resistance via glutathione depletion. Early-phase clinical trials corroborate VC’s safety profile and potential to ameliorate chemotherapy-induced fatigue and nephrotoxicity. However, translational challenges persist, including the lack of pharmacokinetic standardization between oral and intravenous routes, tumor-type-specific response heterogeneity, and incomplete understanding of VC’s immunomodulatory dynamics. Emerging strategies integrating VC with checkpoint inhibitors and TME-targeted nano-delivery systems show promise in preclinical models. This review synthesizes mechanistic insights from redox biology and immunometabolism to clinical trial data, proposing a framework for optimizing VC-based combination therapies while addressing critical gaps in biomarker development and dose scheduling. Deciphering the molecular determinants of VC’s context-dependent anticancer effects may accelerate its rational clinical deployment.